Development of online music courses using A-Tutor - Syntixakis, Eythimios; Kalouta, Kaliopi (Συνέδρια της Ελληνικής Επιστημονικής Ένωσης Τεχνολογιών Πληροφορίας & Επικοινωνιών στην Εκπαίδευση, 2022)
As e-learning evolves and expands, it can address different domains of education. Music is an essential aspect of educating an individual, but when implemented in an e-learning system, it inherits certain challenges of distance and impersonality. In this study we create a music course using existing context from the 5th grade Music Course of the Greek public school curriculum. The course is hosted on an online learning management system, A-Tutor, which provides social network capabilities. Also, we implemented some interactive material to further increase the engagement of the participants.